Electrostatically Stabilized Magnetic Nanoparticles – An Optimized Protocol to Label Murine T Cells for in vivo MRI - Wuerfel, Eva; Smyth, Maureen; Schellenberger, Eyk; Glumm, Jana; Prozorovski, Timour; Aktas, Orhan; Schulze-Topphoff, Ulf; Schnorr, Jörg; Wagner, Susanne; Taupitz, Matthias; Infante, Carmen; Wuerfel, Jens (Frontiers in Neurology, 2011)
We present a novel highly efficient protocol to magnetically label T cells applying electrostatically stabilized very small superparamagnetic iron oxide particles (VSOP). Our long-term aim is to use magnetic resonance imaging (MRI) to investigate T cell dynamics in vivo during the course of neuroinflammatory disorders such as experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. Encephalitogenic T cells were co-incubated with VSOP, or with protamine-complexed VSOP (VProt), respectively, at different conditions, optimizing concentrations and incubation times. Labeling efficacy was determined by atomic absorption spectrometry as well as histologically, and evaluated on a 7 Tesla MR system. Furthermore, we investigated possible alterations of T cell physiology caused by the labeling procedure. T cell co-incubation with VSOP resulted in an efficient cellular iron uptake. T2 times of labeled cells dropped significantly, resulting in prominent hypointensity on T2*-weighted scans. Optimal labeling efficacy was achieved by VProt (1 mM Fe/ml, 8 h incubation; T2 time shortening of ∼ 80 % compared to untreated cells). VSOP promoted T cell proliferation and altered the ratio of T cell subpopulations towards a CD4+ phenotype. VProt yields a highly efficient T cell labeling, adapted for applications in future in vivo trials. High concentrations of intracellular iron oxide might induce alterations in T cell function, which should be considered in cell tagging studies.